Revision of the Australian water flea Ovalona setuloides (Smirnov & Timms, 1983) reveals a relict species-complex within Ovalona Van Damme & Dumont, 2008 (Cladocera: Anomopoda: Chydoridae) - Sinev, Artem Y. (Zootaxa, 2026)
Research into the morphology of the rare Western Australian cladoceran, Alona setuloides Smirnov and Timms, 1983, (Crustacea: Cladocera: Chydoridae), based on type material, led to its translocation to the genus Ovalona Van Damme and Dumont, 2008. O. setuloides is one of the most primitive members of the genus and is a sister species to the Mediterranean Ovalona nuragica (Alonso, 1996). The main synapomorphy between these two species lies in the lateral head pores (in the form of small, rounded cavities), unique to Alona s. lato. These two species also exhibit a morphology similar to that of the Andean Ovalona nigra (Smirnov, 1995). The species in this group are relict, rare, and confined to specific habitats. The current distribution of the nuragica-group can be explained by the “theory of ejected relicts”. The group likely originated in the Mesozoic; it was distributed throughout Mesozoic Gondwana, but is now replaced by the eurybiotic pulchella-clade, the terminal group of Ovalona.